2017
DOI: 10.1002/jso.24580
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase II, open‐label, non‐comparative study of intralesional PV‐10 followed by radiotherapy for the treatment of in‐transit or metastatic melanoma

Abstract: BACKGROUNDIn‐transit and recurrent dermal or subcutaneous melanoma metastases represent a significant burden of advanced disease. Intralesional Rose Bengal can elicit tumor selective ablation and a T‐cell mediated abscopal effect in untreated lesions. A subset of patients in a phase II trial setting received external beam radiotherapy to their recurrent lesions with complete or partial response and no significant acute radiation reaction.METHODSAn open‐label, single‐arm phase II study was performed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 24 publications
(80 reference statements)
6
38
3
Order By: Relevance
“…PV‐10 causes direct tumor lysis, promotes selective lymphocyte‐mediated tumor destruction and is associated with a quantifiable local and systemic anti‐tumor response, including a T‐cell regulated abscopal effect in untreated lesions . PV‐10 has been investigated both as a single agent and in combination therapy with radiotherapy …”
Section: Introductionmentioning
confidence: 99%
“…PV‐10 causes direct tumor lysis, promotes selective lymphocyte‐mediated tumor destruction and is associated with a quantifiable local and systemic anti‐tumor response, including a T‐cell regulated abscopal effect in untreated lesions . PV‐10 has been investigated both as a single agent and in combination therapy with radiotherapy …”
Section: Introductionmentioning
confidence: 99%
“…Table summarizes the key data for each modality and presents the pooled results including the weighted ORR and meta‐analysis data. Assessed studies included: randomized controlled trials, nonrandomized phase I and II comparative and noncomparative studies, and prospective or retrospective case series (NHMRC levels II–IV evidence; Tables S2‐S9) . Only two therapies: amputation and topical imiquimod, were suitable for formal meta‐analysis ( I 2 value ≤ 40%).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a key advantage of PV‐10 appears to be the favorable side effect profile and cost compared with IL‐2 and as an independent agent appears to have no negative impact on quality of life following treatment . These agents can also be used within the outpatient setting and can be combined with radiotherapy and imiquimod with synergism . These therapies are particularly useful for polymetastatic disease and nodular or bulky metastases that are otherwise inaccessible or would require significant surgical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…12 A phase II study of PV-10 in 80 patients with metastatic melanoma reported a local complete response (CR) rate in injected target lesions of 26% with extended periods of local control (mean progression-free survival [PFS] 8.0 months). 14,15 Separately, both treatments have been reported to produced durable responses; however, a prospective study directly comparing long-term outcomes has not yet been performed. 14,15 Separately, both treatments have been reported to produced durable responses; however, a prospective study directly comparing long-term outcomes has not yet been performed.…”
mentioning
confidence: 99%
“…This is relevant because studies have demonstrated that patients with a lower burden of disease experience improved response rates and PFS with treatment 14,15,26. Propensity score matching offers a pragmatic alternative to evaluate the relative treatment effect when conducting a larger adequately powered study is not feasible.There are several limitations to the current study.…”
mentioning
confidence: 99%